Evaluation of the efficacy of probiotics in the chemoradiotherapy of colorectal cancer: a meta-analysis of Randomized Controlled Trials - Rong Yang; Wei Liu; Shuiyan Cai; Xiurong Feng; Yongjing Chen; Xiangyu Cheng; Junjie Ma; Weiyu Ma; Zhihui Tian; Wenhui Yang (BMC Gastroenterology)
Abstract Objective We undertook this study to assess the efficacy of probiotics in managing adverse reactions during chemoradiotherapy in patients with colorectal cancer. Method A comprehensive literature search was conducted on PubMed, ClinicalTrials.gov, Embase, Cochrane library,Web of Science, and Chinese databases until July 27, 2024. Data analysis was performed using RevMan5.3 statistical software. The risk of bias was assessed using the Cochrane collaboration tool. Relative risk (RR) was employed to incorporate statistical measures and calculate 95% confidence intervals (95%CI) for bipartite data. Standardized mean difference (SMD) was utilized to incorporate statistical measures and calculate 95% confidence intervals for continuous variables. Results A meta-analysis of 633 patients with colorectal cancer was conducted across eight studies. In comparison to the control group, probiotics demonstrated a significant reduction in the incidence of chemoradiotherapy-induced diarrhea among colorectal cancer patients(RR = 0.51,95%Cl:0.38 ~ 0.68,P < 0.001). Additionally, probiotic usage exhibited improvements in pain index (SMD = -2.27,95%Cl: -4.49 ~ -0.05,P = 0.04), dyspnea (SMD = -0.92,95%Cl: -1.61 ~ 0.22, P = 0.01) and insomnia (SMD = -2.95, 95%Cl: -5.44 ~ -0.47, P = 0.02) compared to the control group. However, there were no significant differences between two groups in abdominal distension(RR = 0.79, 95%Cl:0.21 ~ 3.00, P = 0.72), stomatitis risk (RR = 1.23, 95%Cl: 0.48 ~ 3.21, P = 0.67), fatigue (SMD = -7.12, 95%Cl:-14.99 ~ 0.75, P = 0.08)and loss of appetite(SMD = -2.86, 95%Cl: -5.83 ~ 0.11, P = 0.06). Furthermore, the use of probiotics did not significantly improve the quality of life (QOL) (SMD = 8.82, 95%Cl: -1.11 ~ 18.75, P = 0.08)of colorectal cancer patients receiving chemoradiotherapy. Conclusions This meta-analysis suggested that probiotic consumption may ameliorate certain adverse reactions in patients with colorectal cancer receiving chemoradiotherapy. Trial registrations Prospero registration number: PROSPERO (CRD42023465966).